2020
DOI: 10.1080/17461391.2020.1771429
|View full text |Cite
|
Sign up to set email alerts
|

Coldzyme® Mouth Spray reduces duration of upper respiratory tract infection symptoms in endurance athletes under free living conditions

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 38 publications
(73 reference statements)
4
16
0
4
Order By: Relevance
“…In a smaller open-label study in athletes, the proportions of virus-protected persons per treatment group were not released, but there was no significant difference in number of CC episodes/person between the CZ-MD and control group [ 53 ]. The study mixing (unweighted) data obtained from winter seasons over 2 years claimed a reduction of 3.5 days with CZ-MD versus the controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a smaller open-label study in athletes, the proportions of virus-protected persons per treatment group were not released, but there was no significant difference in number of CC episodes/person between the CZ-MD and control group [ 53 ]. The study mixing (unweighted) data obtained from winter seasons over 2 years claimed a reduction of 3.5 days with CZ-MD versus the controls.…”
Section: Resultsmentioning
confidence: 99%
“…Isolated adverse effects reported in the studies included labial Herpes simplex infection and urticaria, not related to the MD [ 54 ] and unsettled stomach, potentially related [ 53 ]. In the prospective trial NCT03831763 reporting on 267 of the 400 targeted participants, the manufacturer’s press release discloses: “no side effects attributable to ColdZyme were reported”.…”
Section: Resultsmentioning
confidence: 99%
“…Coronaviruses cause about one‐third of the common cold cases 4 . The efficacy and safety of CZ‐MD against the common cold have been demonstrated in clinical trials 9,10 . Furthermore, active SARS‐CoV‐2 replication in the upper respiratory tract was demonstrated in patients suffering from COVID‐19 with high virus shedding 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The CZ‐MD is believed to act on the viral surface proteins that would perturb their entry pathway into cells 8 . Clinical trials demonstrate the safety and efficacy of CZ‐MD against the common cold 9,10 . Also, in vitro studies have shown inactivation of respiratory viruses such as rhinovirus (HRV), respiratory syncytial virus (RSV), and influenza by the CZ‐MD 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation